Correlation between Ascaris Lumbricoides Infection and The Results of Skin Prick Test using Allergen from Ascaris Worms in Students of Koto Baru 047/XI Elementary School with Atopic History in Pesisir Bukit Sub-District Sungai Penuh City Jambi Province - Rachman, Faisal; Depari, Aman A.P.; Arrasyid, Nurfida Khairina (Universitas Muhammadiyah Sumatera Utara, 2021)
Infectious diseases, intestinal worms that are transmitted through the soil (Soil-transmitted helminthiasis) is common infection that involves many people in the world. Estimates suggest Ascaris lumbricoides infect over one billion people. The number of most worm infections apply to sub-Saharan Africa, the Americas, China, and East Asia. The prevalence of asthma and other atopic diseases in children has increased worldwide in recent years, but the reason behind the increase in prevalence is unknown. Most epidemiologic data derived from research centers in the west while in Indonesia have not been many reports on the prevalence of allergies, especially when associated with parasitic infections. Ascaris lumbricoides infections induce immune responses that lead to the production of immunoglobulin type E (IgE) in large numbers. Atopy can be diagnosed by an individual or a family history that confirmed the presence of allergen-specific IgE or skin prick test results were positive. Conducted this study to compare the proportion of atopy in children infected with Ascaris lumbricoides were not infected with the cross-sectional method and determine the relationship between Ascaris lumbricoides infection of the skin prick test results with the allergen of Ascaris on elementary school children 047/XI Koto Baru with a history of atopy in the Coastal Hills District Full River City Jambi Province. Of 258 students overall, as many as 220 students and are willing to meet the requirements of the study examined stool. On a stool examination, 220 students found that Ascaris lumbricoides infections by 67 students and non-patient infection of Ascaris lumbricoides at 153 students. There is a relationship between Ascaris lumbricoides infection of a positive skin prick test results with the allergen of Ascaris on elementary school children 047/XI Koto Baru with a history of atopy in the Coastal Hills District Full River City Jambi Province namely in children infected with Ascaris lumbricoides was 67 (100% ) significantly different compared with uninfected children Ascaris lumbricoides 153 (100%) (p=0.0001)